Progress in the Chemistry of Organic Natural Products 104 - Kinghorn, A. Douglas; Falk, Heinz; Gibbons, Simon; Kobayashi, Jun'ichi.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The first contribution describes apolar and polar molecular fossils and, in particular biomarkers, along the lines usually followed in organic chemistry textbooks, and points to their bioprecursors when available. Thus, the apolar compounds are divided in linear and branched alkanes followed by alicyclic compounds and aromatic and heterocyclic molecules, and, in particular, the geoporphyrins. The polar molecular fossils contain as functional groups or constituent units ethers, alcohols, phenols, carbonyl groups, flavonoids, quinones, and acids, or are polymers like kerogen, amber, melanin, proteins, or nucleic acids. The final sections discuss the methodology used and the fundamental processes encountered by the biomolecules described, including diagenesis, catagenesis, and metagenesis. The second contribution covers the distribution of phthalides in nature and the findings in the structural diversity, chemical reactivity, biotransformations, syntheses, and bioactivity of natural and semisynthetic phthalides.
Keywords: Chemistry, Organic; Pharmaceutical chemistry; Medicinal chemistry; Organic Chemistry; Pharmaceutics; Medicinal Chemistry